2005
DOI: 10.1002/cncr.21551
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral breast tumor recurrence (IBTR) after breast‐conserving treatment for early breast cancer

Abstract: BACKGROUNDThe clinical features of ipsilateral breast tumor recurrence (IBTR) after breast conserving therapy (BCT) for early stage breast cancer were analyzed from long‐term follow‐up of BCT in Japan. The purpose of this study was to clarify risk factors of IBTR and the impact of IBTR on development of distant metastases in this ethnic group.METHODSPatients (N = 1901)with unilateral breast cancer ≤ 3 cm in diameter who underwent BCT at 18 Japanese major breast cancer treatment institutes from 1986 to 1993 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
3
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(122 citation statements)
references
References 48 publications
7
107
3
5
Order By: Relevance
“…[6][7][8][9][10] The most frequently identified factors include young age, presence of an extensive intraductal component (EIC), and a positive resection margin. [6][7][8][9][10] RT reduces the risk of locoregional breast cancer recurrence approximately 70% and improves survival compared to surgery alone. 11 A booster radiation dose to the tumour site reduces further the IBR rate after breast conserving surgery, especially among premenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] The most frequently identified factors include young age, presence of an extensive intraductal component (EIC), and a positive resection margin. [6][7][8][9][10] RT reduces the risk of locoregional breast cancer recurrence approximately 70% and improves survival compared to surgery alone. 11 A booster radiation dose to the tumour site reduces further the IBR rate after breast conserving surgery, especially among premenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The addition of a radiation boost after whole-breast irradiation and adjuvant systemic therapy reduces LR rates by 40% to 60%, especially in younger patients (9,11,16,17,19,20).…”
mentioning
confidence: 99%
“…Other series also confirmed that young age is associated with increased risk for local recurrence after BCS [58][59][60] . Nevertheless, a recent population-based study from The Netherlands showed that five-year rates of developing local or regional recurrence in women < 35 years of age were only 3.5 and 3.7%, respectively 61 .…”
Section: Surgical Treatmentmentioning
confidence: 59%